2015
DOI: 10.1093/mnrasl/slv096
|View full text |Cite
|
Sign up to set email alerts
|

Detection of magnetic fields in both B-type components of the ϵ Lupi system: a new constraint on the origin of fossil fields?

Abstract: High-resolution circular spectropolarimetric observations, obtained with ESPaDOnS in the context of the BinaMIcS Large Program, have revealed a magnetic field in the B3V secondary component of the SB2 binary system ǫ Lupi (B2/B3). As the B2V primary is already known to be magnetic, this is the first detection of a magnetic field in both components of an early-type binary system. The longitudinal magnetic field of the primary is ∼ −200 G; that of the secondary ∼ +100 G. Observations can be approximately reprodu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…The three binary stars showing Hα-emission are all very young, and their CMs are no larger than single Hα-bright stars of comparable ages (Shultz et al 2019c). The two close binary systems without Hα emission, HD 136504 (in which system both components are magnetic, Shultz et al 2015) and HD 149277, are middle-aged and have CMs that are somewhat smaller than the average of their contemporaries.…”
Section: Evolution Of Rotation and Confinementmentioning
confidence: 99%
“…The three binary stars showing Hα-emission are all very young, and their CMs are no larger than single Hα-bright stars of comparable ages (Shultz et al 2019c). The two close binary systems without Hα emission, HD 136504 (in which system both components are magnetic, Shultz et al 2015) and HD 149277, are middle-aged and have CMs that are somewhat smaller than the average of their contemporaries.…”
Section: Evolution Of Rotation and Confinementmentioning
confidence: 99%
“…Carrier et al (2002) in Ap stars and now confirmed by the BinaMIcS project in more massive OB stars: the magnetic incidence in close, massive binaries is no more than about 2% (Neiner & Alecian 2013;Alecian et al 2015;Neiner et al 2015). As of today there is only one binary with a magnetic field detection in both components, the eccentric (e = 0.27), 4.56 d B-star binary Lupi (Shultz et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Landstreet & Mathys 2000), we can wonder whether the small β value is another consequence of tidal interactions. Interestingly, two other close binary systems containing magnetic Ap/Bp stars, Lup (Shultz et al 2015) and HD 5550 (Alecian et al 2016), also share the characteristic of magnetic fields having small values of β.…”
mentioning
confidence: 99%